2009
DOI: 10.1353/hpu.0.0231
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Diabetes Care at a Student-Run Free Clinic

Abstract: Student-run clinics are emerging safety-net practices for the uninsured; despite the over 110 clinics that currently operate across the United States, however, no data exist on the quality of care being delivered at such sites. The East Harlem Health Outreach Partnership (EHHOP) of the Mount Sinai School of Medicine in New York is a medical student-run, attending-supervised free clinic that offers primary care to the uninsured of surrounding East Harlem. The aim of this study was to evaluate diabetes care qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…These partnerships have the potential to improve public health and address social determinants of health utilizing a multidimensional approach to health care. Student-led organizations have been demonstrated to provide high-quality care as prescribed by national standards 36,37. With the support and guidance of academic institutions and community partnerships, motivated students can utilize their knowledge and skill sets to work on an interdisciplinary team to meet public health needs.…”
Section: Discussionmentioning
confidence: 99%
“…These partnerships have the potential to improve public health and address social determinants of health utilizing a multidimensional approach to health care. Student-led organizations have been demonstrated to provide high-quality care as prescribed by national standards 36,37. With the support and guidance of academic institutions and community partnerships, motivated students can utilize their knowledge and skill sets to work on an interdisciplinary team to meet public health needs.…”
Section: Discussionmentioning
confidence: 99%
“…Prompts for preventive screening may be more successful in a clinic run by medical students where education and clinical service resource constraints may allow increased concentration on more acute priorities [14]. Studies have found student-run free clinics have successful attainment in intermediate clinical outcomes for patients with chronic disease [15]. In addition, free clinic standards outperform published standards for chronic diseases, such as diabetes [16].…”
Section: Free Clinicsmentioning
confidence: 99%
“…At SRFCs, a student often performs the initial patient evaluation before presenting the case to a qualified clinician. Past studies have shown SRFCs to be a feasible and effective means of providing care to uninsured, poverty-stricken, or otherwise vulnerable populations [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%